Ответ:
sin 70°
Объяснение:
по формуле разности аргументов синуса:
[tex] \sin( \alpha ) \cos( \beta ) - \cos( \alpha ) \sin( \beta ) = \sin( \alpha - \beta ) [/tex]
и по формуле двойного угла синуса:
[tex]2 \sin( \alpha ) \cos( \alpha ) = \sin(2 \alpha ) [/tex]
упростим дробь:
[tex] \frac{ {( \sin100 \cos30 - \cos100\sin30) }^{2} }{2 \sin35 \cos35} = \frac{ { \sin(100 - 30) }^{2} }{ \sin(2 \times 35) } = \frac{ { \sin(70) }^{2} }{ \sin(70) } = \sin(70) [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
sin 70°
Объяснение:
по формуле разности аргументов синуса:
[tex] \sin( \alpha ) \cos( \beta ) - \cos( \alpha ) \sin( \beta ) = \sin( \alpha - \beta ) [/tex]
и по формуле двойного угла синуса:
[tex]2 \sin( \alpha ) \cos( \alpha ) = \sin(2 \alpha ) [/tex]
упростим дробь:
[tex] \frac{ {( \sin100 \cos30 - \cos100\sin30) }^{2} }{2 \sin35 \cos35} = \frac{ { \sin(100 - 30) }^{2} }{ \sin(2 \times 35) } = \frac{ { \sin(70) }^{2} }{ \sin(70) } = \sin(70) [/tex]